Anestesi Spinal pada Sectio Caesarea dengan indikasi Preeklampsia Berat: Sebuah Laporan Kasus - Ari Wahyuni; Devi Octiara (Medula, 2021)
Severe preeclampsia is a disorder that occurs at the age of 20 weeks of pregnancy until approaching labor characterized by systolic blood pressure ≥160 mmHg and diastolic blood pressure ≥110 mmHg, proteinuria ≥2+ on dipstick, platelets <100.000/μL, elevated levels of liver enzymes; AST and ALT, oliguria <400 ml/24 hours, creatinine serum >1.2 mg/dl, epigastric pain, pulmonary edema, headaches in the frontal region, diplopia or blurred vision, and retinal bleeding. Pre-survey results in 2016 at H. Abdul Moeloek Regional Hospital in Lampung Province as many as 46 cases of maternal deaths caused by preeclampsia. Delay in handling the patient can cause worsening conditions for the mother and fetus so that many emergency conditions that force labor must be done by sectio caesarea (SC). Sectio caesarea is a method for delivering babies through incisions in the abdomen and uterus. In sectio caesarea, regional spinal anesthesia is generally chosen because it has many advantages. The method of management of spinal anesthesia is obtained by injecting local anesthetic drugs directly into the cerebro spinal fluid in the subarachnoid space. Mrs. L, age 28 years came with complaints of heartburn since 20 hours before being admitted to the hospital accompanied by high blood pressure that appeared since the age of 7 months of pregnancy. Patients performed sectio caesarea with some consideration of previous anesthesia. Good preoperative, intraoperative, and postoperative management will make this caesarean section successful and unobstructed.